Sistem Penyelenggaraan Makanan pada Keluarga Nelayan yang Memiliki Anak Balita di Kepulauan Masaloka Raya Kabupaten Bombana - Asni, Nurul; Demmalewa, Jenny Qlifianti; Dhesa, Desiderius Bella (Sekolah Tinggi Ilmu Kesehatan Karya Kesehatan, 2024)
Nutritional problems in the coastal area of ​​the Masaloka Raya Health Center are very high, the prevalence of stunting is 27.7% wasting 19%. 0.4% overweight and 34.9% underweight. The food management system for fishermen's families also plays a role in determining the nutritional problems of coastal communities, especially in the aspects of purchasing, cooking and distributing food. The purpose of this study was to determine the food management system by mothers in fishing families in the Masaloka Raya Islands, Bombana Regency. This type of research is descriptive, cross-sectional study approach. This research was conducted in Masaloka Raya Village in August 2024. The population was all toddlers in the Masaloka Health Center area, which was 84 people and the sample was some toddlers as many as 34 people who were taken using the simple random sampling technique. Data were collected using a valid and reliable questionnaire and analyzed descriptively. The results of the study found that the food purchasing system in fishing families was mostly in the sufficient category (91.2%), the rest was lacking (8.8%). The cooking system was mostly lacking (52.9%) and the rest (47.1%). The food distribution system was 100% sufficient. The conclusion of this study is that the food purchasing and distribution system is in the good category while the cooking system is mostly lacking. Suggestions for fishing families are to buy local vegetables and fruits so that nutritional needs are met in a balanced way and not to use food flavor enhancers such as royko or Masako. For Masaloka Raya Village to provide education related to balanced nutrition and for further researchers, to statistically analyze the causes of the lack of food cooking systems for fishing families in the coastal areas of the Masaloka Islands.